Influence of Bilateral Subthalamic Nucleus Deep Brain Stimulation on the Lipid Profile in Patients With Parkinson's Disease - Samborska-Ćwik, Joanna; Szlufik, Stanisław; Friedman, Andrzej; Mandat, Tomasz; Przybyszewski, Andrzej; Koziorowski, Dariusz (Frontiers in Neurology, 2020)
Background: Subthalamic nucleus deep brain stimulation (STN-DBS) is a valuable alternative to pharmacotherapy alone in advanced Parkinson’s disease (PD). Given the growing number of patients with STN-DBS its impact on comorbidities should be considered. Aim: The aim of this study was to evaluate the influence of bilateral STN-DBS on lipid profile in patients with PD. Methods: Three groups of parkinsonian patients were included: 20 treated pharmacologically - PHT group, 20 newly qualified for STN-DBS - DBS group and 14 postoperative patients (median 30 months after surgery) – POP group. Plasma concentrations of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG) and body weight were measured thrice in 9±2 month intervals. Results: Significant increase in LDL-C concentration is observed early after surgery in the DBS group (11.4 mg/dl, P<0.01) followed by adverse changes in HDL-C (-7.7 mg/dl, P=0.01) and TG (14.1 mg/dl, P=0.05) plasma levels. In the POP group the average level of TC at the first visit was significantly higher (P<0.01) than in other groups and the TG level was higher than in the PHT group during follow-up (P<0.01). A strong positive correlation with body weight alteration after surgery was observed only for long-term changes in TG levels. Conclusions: Our data indicate that STN-DBS may negatively affect the cardiometabolic profile of patients. Similarly to body weight gain, increase in LDL-C concentration occurred early after surgery while adverse changes in HDL-C and TG plasma levels were more gradual.